PENGARUH MODEL PROBLEM BASED LEARNING (PBL) DISERTAI VIDEO BERBASIS KONTEKSTUAL TERHADAP HASIL BELAJAR DAN KETERAMPILAN PROSES SAINS DALAM PEMBELAJARAN FISIKA DI SMA - Khantika Andriani; Subiki Subiki; Bambang Supriadi (JURNAL PEMBELAJARAN FISIKA, 2021)
This research aims: (1) to examine the influence of problem based learning models along with contextual-based videos on the learning outcomes of students in physics learning in sma (2) examining the influence of problem based learning models along with contextual-based videos on the science process skills of students in high school learning. The research model used is true experiment with posttest only control design research design. The research samples used are class X IPA 2 (experiment class) and X IPA 1 (control class) of Tamanan State High School. Data obtained include posttest results and science process skills scores. The data is analyzed with statistics consisting of homogeneity tests, normality tests, and independent sample t-test tests. From an independent sample t-test analysis obtained significantly (sig2-tailed) by 0,000 (0.000 ≤ 0.05), it can be concluded Ho was rejected and Ha accepted that there was a difference in the learning outcomes of the experiment class students better than the control class. This can be seen from the average posttest score of the experiment class of 72.48 while the average posttest value of the control class is 48.87. Based on the results of analysis of science process skills students through two experiments obtained scores in a row of 76.61 and 77.42 in the excellent category. Thus the problem based learning model accompanied by contextual-based video affects the learning outcomes and science process skills of students in high school. Keywords: Problem Based Learning, Contextual Video, Physics Learning